2014
DOI: 10.1039/c4ta03426k
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted growth of In2O3 nanoparticles on WO3 nanoplates to improve H2S-sensing performance

Abstract: Hierarchical In 2 O 3 @WO 3 nanocomposites, consisting of discrete In 2 O 3 nanoparticles (NPs) on singlecrystal WO 3 nanoplates, were synthesized via a novel microwave-assisted growth of In 2 O 3 NPs on the surfaces of WO 3 nanoplates that were derived through an intercalation and topochemical-conversion route. The techniques of XRD, SEM, TEM and XPS were used to characterize the samples obtained. The gas-sensing properties of In 2 O 3 @WO 3 nanocomposites, together with WO 3 nanoplates and In 2 O 3 nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 51 publications
(82 reference statements)
1
32
0
Order By: Relevance
“…The W 4f specturm (Fig. 4c) was composed of two obvious peaks at 36.0 and 37.9 eV, belonging to W 4f 7/2 and W f 5/2 of WO 3 , respectively [9]. The O 1s peak was asymmetric and could be fitted into two components.…”
Section: Structural and Morphological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The W 4f specturm (Fig. 4c) was composed of two obvious peaks at 36.0 and 37.9 eV, belonging to W 4f 7/2 and W f 5/2 of WO 3 , respectively [9]. The O 1s peak was asymmetric and could be fitted into two components.…”
Section: Structural and Morphological Characteristicsmentioning
confidence: 99%
“…Resistive gas sensors based on metal oxide semiconductors such as SnO 2 [1,2], ZnO [3,4], TiO 2 [5,6], WO 3 [7][8][9][10][11][12], In 2 O 3 [13,14], α-Fe 2 O 3 [15], and NiO [16] occupy the significant positions in the field of gas sensors for monitoring and detecting inflammable, explosive, or toxic gases due to the advantages of low cost, simple operation and portability. Extensive research efforts have been committed to develop high-performance gas sensors with high sensitivity and low detection limit [17].…”
Section: Introductionmentioning
confidence: 99%
“…9 As an n-type wide band-gap (2.6-3.2 eV) semiconductor, tungsten trioxide (WO 3 ) has been widely studied and found that exhibited considerably application prospects in the field of detecting hazardous gases. [10][11][12][13][14][15][16] In the past few years, WO 3 -based sensors with different morphologies have been prepared using various techniques such as CVD, template-carbonization, sputtering, sol-gel, pyrolysis, and hydrothermal. [17][18][19][20][21][22] However it still remains a significant challenge to develop a facile method to prepare shape-controlled hierarchical WO 3 -based sensors with better performance from low-dimensional nanocrystals via selfassembly.…”
Section: Introductionmentioning
confidence: 99%
“…3(b), could originate from IneO bond or AgeO bond. Some reports [36,37] ascribed the similar peak position to the lattice oxygen in IneOeIn bonds of In 2 O 3 species. In this paper, the high-resolution Ag 3d core level spectrum shows two XPS peaks at 374.1 eV and 368.1 eV in Fig.…”
Section: Conversion Of the Stiff Gel Into The Glassmentioning
confidence: 91%